# 1.) Evaluate the indicated function, where f(x) = x2 − 8x + 3and g(x) = 7x − 5. (f + g)(5)= 2.) Evaluate the indicated function,

###### Question:

(f + g)(5)=

2.) Evaluate the indicated function, where f(x) = x2 − 7x + 4 and g(x) = 6x − 7.

(f + g)(1/2)=

3.) Evaluate the indicated function, where f(x) = x2 − 3x + 4 and g(x) = 4x − 2.

(f − g)(−1)=

4.) Evaluate the indicated function, where f(x) = x2 − 4x + 3and g(x) = 3x − 2.

(fg)(7)=

5.) Evaluate the indicated function, where f(x) = x2 − 3x + 2and g(x) = 4x − 8.

(f/g)(−2)=

6.) Find (g ○ f)(x) and (f ○ g)(x) for the given functions f and g. f(x) = 2x − 8, g(x) = 3x + 1

7.) Find (g ○ f)(x) and (f ○ g)(x) for the given functions f and g.

f(x) = 3/x+5, g(x) = 3x − 6

8.) Evaluate the composite function, where f(x) = 2x + 3,g(x) = x2 − 5x, and h(x) = 4 − 3x2.

(f ○ g)(5)=

## Answers

1) (f + g) (5) = 18, 2) (f + g) (1/2) = - 13/4, 3) (f - g) (-1) = 14, 4) (f * g) (7) = 456, 5) (f/g) (- 2) = - 3/4, 6) (g ○ f)(x) = 6 x - 23, (f ○ g)(x) = 6 x - 6, 7) [tex](g \circ f) (x) = \frac{9}{x} - 24[/tex], [tex](f \circ g) (x) = \frac{1}{x - 2} + 5[/tex], 8) (f ○ g)(5) = 3

Step-by-step explanation:

1) [tex](f + g) (x) = x^{2}-8\cdot x + 3 + 7 \cdot x - 5\\(f + g) (x) = x^{2} - x - 2\\(f + g) (5) = 18[/tex]

2) [tex](f + g) (x) = x^{2} - 7 \cdot x + 4 + 6 \cdot x - 7\\(f + g) (x) = x^{2} - x - 3\\(f + g) (\frac{1}{2} ) = - \frac{13}{4}[/tex]

3) [tex](f - g) (x) = x^{2} - 3 \cdot x + 4 - 4 \cdot x + 2\\(f - g) (x) = x^{2} - 7 \cdot x + 6\\(f - g) (-1) = 14[/tex]

4) [tex](f \cdot g) (x) = (x^{2}-4\cdot x + 3) \cdot (3\cdot x - 2)\\(f \cdot g) (7) = 456[/tex]

5) [tex](f / g) (x) = \frac{x^{2}-3\cdot x + 2}{4 \cdot x - 8} \\(f / g) (-2) = - \frac{3}{4}[/tex]

6) [tex](g \circ f) (x) = 3 \cdot (2 \cdot x - 8) + 1\\(g \circ f) (x) = 6 \cdot x - 23\\(f \circ g) (x) = 2 \cdot (3 \cdot x + 1) - 8\\(f \circ g) (x) = 6 \cdot x - 6[/tex]

7) [tex](g \circ f) (x) = 3 \cdot (\frac{3}{x} - 6) - 6\\(g \circ f) (x) = \frac{9}{x} - 24\\(f \circ g) (x) = \frac{3}{3 \cdot x - 6} + 5\\(f \circ g) (x) = \frac{1}{x - 2} + 5[/tex]

8) [tex](f \circ g) (x) = 2 \cdot (x^{2} - 5 \cdot x) + 3\\(f \circ g) (x) = 2 \cdot x ^{2} - 10 \cdot x + 3\\(f \circ g) (5) = 3[/tex]

people in Africa. African nations typically fall toward the bottom of any list measuring small size economic activity, such as income per capita or GDP per capita, despite a wealth of natural resources

Step-by-step explanation:

f(- 1) = 14

Step-by-step explanation:

To evaluate f(- 1) substitute x = - 1 into f(x)

f(- 1) = (- 1)² - 8(- 1) + 5 = 1 + 8 + 5 = 14

f(-1)=14

14-4=25

13=70

Step-by-step explanation:

k= one half

Step-by-step explanation:

f(x) = x² - 8x + 5 Plug in -1 for all of the x-values

f(-1) = (-1)² - 8 (-1) + 5 Square -1

f(-1) = 1 - 8 (-1) + 5 Multiply -8 and -1

f(-1) = 1 + 8 + 5 Add

f(-1) = 14